PERAMALAN INDEKS HARGA KONSUMEN DAN INFLASI INDONESIA DENGAN METODE ARIMA BOX-JENKINS - Tripena, Agustini (MAGISTRA, 2011)
In this paper, forecasting the consumer price index data and inflation. The method used Box-JenkinsARIMA. For data that belongs there more than one model that can be used the method of ARIMA (1, 1, 0),ARIMA (0, 1, 1), and ARIMA (1, 1, 1). Thus the value of AIC, ARIMA (1, 1, 1) is the best method for data andconsumer price index inflationThe results showed that the forecast value of the consumer price index based on the model ARIMA (1, 1,1) is for May 2009 was 175.82, in June 2009 was 176.63, and in July 2009 was 177, 65 While the forecastinflation for the month May 2009 is -0.05, June 2009  4105 ??? , and July 2009  4105,5 ??? .Keywords : CPI, inflation, time series, forecasting, ARIMA, AIC